Pengaruh Edukasi Dash Menggunakan Leaflet terhadap Pengetahuan, Sikap, Pola Makan dan Tekanan Darah pada Pasien Hipertensi - Dwi Astuti; Yunita Nazarena; Podojoyo Podojoyo (Jurnal Sehat Mandiri, 2025)
Hypertension is a chronic disease with increasing prevalence in Indonesia, including Pangkalpinang City. Risk factors can be controlled through diet, one of which is the DASH diet. Education using leaflets is needed to improve the knowledge, attitudes, and dietary patterns of hypertensive patients. The aim was to determine the effect of DASH education using leaflets on knowledge, attitudes, dietary patterns, and blood pressure of hypertensive patients in Bukit Besar Village. This pre-experimental study used a one-group pretest-posttest design. The population was 921 patients with hypertension. The sampling technique was simple random sampling of 96 people with hypertension in Bukit Besar Village, Pangkalpinang City, Bangka Belitung Province. Analyzed using SPSS version 17 for Windows with a Paired Sample t-test. The results of DASH education using leaflets on knowledge (0.000), attitudes (0.000), dietary patterns (0.000), systolic blood pressure (0.000) (<0.05), and diastolic blood pressure 0.545 (>0.05). There is an effect of DASH education using leaflets on knowledge, attitudes, eating patterns, and systolic blood pressure of hypertensive patients .There is no effect of DASH education using leaflets on diastolic blood pressure of hypertensive patients. Hypertensive patients in Bukit Besar Village, Pangkalpinang City, Bangka Belitung Province.are expected to apply the DASH diet in their daily lives, manage stress, and maintain rest. Increased education, monitoring, and routine blood pressure checks are needed to prevent the high prevalence of hypertension.